The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/su12135351
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Economy and Lifestyle Changes, as Exemplified by the Tourism Market

Abstract: The aim of the article is to analyze the relationship between lifestyle changes and willingness to use sharing economy services in tourism, including peer-to-peer accommodation. On the one hand, knowledge of lifestyle changes can help adapt the product offer to the requirements of consumers. On the other hand, products that consumers use can reflect lifestyle changes. The following classification of motivations for sharing economy activity selection resulting from the subjects’ lifestyles has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Milanova and Maas [46] suggest that factors that motivate consumer participation in the sharing economy are social, economic, and technological. More recently, Niezgoda and Kowalska [4] support this view by highlighting personal, social, and ideological factors. Specifically, Tussyadiah [47] found that sustainability, community, and economic benefits are three main factors that motivate users to stay in Airbnb accommodations.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…Milanova and Maas [46] suggest that factors that motivate consumer participation in the sharing economy are social, economic, and technological. More recently, Niezgoda and Kowalska [4] support this view by highlighting personal, social, and ideological factors. Specifically, Tussyadiah [47] found that sustainability, community, and economic benefits are three main factors that motivate users to stay in Airbnb accommodations.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The sharing economy is considered to be a new business paradigm and a new form of commerce [1][2][3]. There is no universally accepted definition of the sharing economy, and different terms are used to refer to the same phenomenon [4,5]. In the complete and recent conceptual revision carried out by Schlagwein, Schoder, and Spindeldreher in 2020, the sharing economy is defined as a commercial or non-commercial peer-to-peer model facilitated by an intermediary [3] (p. 12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers are motivated by creating better community and increase sustainability [13]. Some scholars took into consideration lifestyle as motivation to participate: personal motivationeconomic advantages, social motivations -to be like others, and ideological motivationsto help the world [14]. People participation in sharing economy can be also motivated by values: inner symbolic, hedonic and economic values.…”
Section: Introductionmentioning
confidence: 99%
“…Older wealthy subjects, have lifestyle motivation to participate in sharing economy that is rooted in conformist social motivation. Younger subjects are opened to new experiences, older respondents were looking for economic benefits and convenience [14]. Younger people who are environmentally and healthy conscious, take risk and have positive relationship toward digitalisation, are more willing to participate in sharing economy [15].…”
Section: Introductionmentioning
confidence: 99%